2006
DOI: 10.1016/j.pain.2006.01.040
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of headache is related to sensitization: A population study

Abstract: Central sensitization is thought to play an important role in the chronification of tension-type headache and in the maintenance and exacerbation of the migraine attack. It has, however, almost exclusively been studied in highly selected patients from headache clinics. The aim of the present study was to evaluate pain perception in primary headaches in the general population. Stimulus-response functions for pressure versus pain, tenderness and pressure pain thresholds were studied in a random sample of 523 adu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
109
4
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 122 publications
(130 citation statements)
references
References 30 publications
15
109
4
2
Order By: Relevance
“…In disagreement with our results, Buchgreitz et al 4 reported an association between increased muscle tenderness and headache chronification, but the authors did not evaluate episodic and chronic migraine patients. Our findings also disagree with a large populational study, where central sensitization was assessed using a validated questionnaire 29 .…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…In disagreement with our results, Buchgreitz et al 4 reported an association between increased muscle tenderness and headache chronification, but the authors did not evaluate episodic and chronic migraine patients. Our findings also disagree with a large populational study, where central sensitization was assessed using a validated questionnaire 29 .…”
Section: Discussioncontrasting
confidence: 99%
“…Prolonged nociceptive input from the periphery may be associated to the onset of central sensitization, may exacerbate already established central sensitization, and may impair supraspinal pain modulation, since the hyperexcitability could contribute to an amplification of the nociceptive signal coming from the periphery 4,27 . As a result peripheral nociceptive inputs from the face and cervical sites, contributing or not to central sensitization may have influenced the lower PPT values showed in EM and CM groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This amplification also occurs during migraine attacks 108 and worsens with increasing attack frequency. 109 One mechanism underlying central sensi tization is the activity dependent change in excitability of central nociceptors, which results in abnormal ampli fication of pain sensation in physiological nociceptiona phenomenon referred to as temporal summation of pain stimuli 110 that is equivalent to 'wind up' phenomenon (facilitation of wide dynamic range nociceptive neurons located in the deep laminae of the spinal cord dorsal horn and the spinal trigeminal nucleus after constant intensity stimulation of C fibres) in animal experiments. 111 The nociceptive flexion or withdrawal reflex (NWR) is a reliable measure of spinal nociception, as demon strated by the fact that it requires Aδ fibre activation, that the reflex threshold is related to the pain percep tion threshold, and that the reflex magnitude correlates positively with pain intensity ratings.…”
Section: Processing Of Noxious Stimulimentioning
confidence: 99%